HUBUNGAN PELAYANAN KEPENDETAAN TERHADAP TINGKAT KERAJINAN BERIBADAH ANGGOTA GMAHK JEMAAT YORDAN AIRMADIDI - Desy Tris Tatengkeng; Juwinner Dedy Kasingku; Andrew Christian Aseng; Robert Siby (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A pastor is a spiritual leader in the Christian faith who is responsible for religious services and regularly connects with church members. Currently, issues related to pastoral services are considered one of the reasons why church members are less diligent in attending worship. Therefore, a pastor is expected to have a servant-hearted attitude. The purpose of this study is to find out whether there is a relationship between pastoral service and the level of worship attendance among members of the Jordan Airmadidi Seventh-day Adventist Church. This study uses a quantitative method with a descriptive correlational design and a cross-sectional approach. The sampling was done using the convenience sampling technique, with a total of 65 respondents. The results show that overall, the quality of pastoral service at the Jordan Airmadidi Church is categorized as High (average score of 4.23), and the level of worship attendance is also categorized as High (average score of 3.96). Statistical analysis using Pearson correlation shows a significant relationship between pastoral service and worship attendance (p-value = 0.000 < 0.05; correlation coefficient r = 0.573). It is recommended that pastors maintain and continue to improve their ministry, especially in preaching and visiting church members. Church members are also encouraged to consistently participate in worship activities to enhance and deepen their spiritual experience.